Green and glam: Celebritisation of environmental activism on instagram - Rahmawati, Aulia; Febriyanti, Syafrida Nurrachmi; Fitria, Belinda Firda Mila; Hanan, Haris; Pambudi, Gregorius Satrio Adi Arto (Bricolage : Jurnal Magister Ilmu Komunikasi, 2024)
This study examines the celebritization of environmental activism on Instagram, focusing on two prominent Indonesian public figures: Hamish Daud and Nadine Chandrawinata. Through a qualitative discourse analysis of their Instagram posts from July to December 2023, we explore how environmentalsustainability is intertwined with the process of celebritization in the Indonesian context. Drawing on Driessens' (2013) framework of mediatization, personalization, and commodification, and employing Stuart Hall's encoding/decoding model, this research investigates how these celebrities construct and promote their environmental activist personas through social media. Our findings reveal that Daud and Chandrawinata strategically blend their celebrity status with environmental messaging, creating a unique form of 'celebrity ecology'. They leverage Instagram's visual and narrative features to present environmental activism as part of an aspirational yet attainable lifestyle. The study identifies key strategies employed by these celebrities, including the integration of activism with personal branding, the use of family narratives to promote eco-friendly practices, and the endorsement of sustainable products. While their approach effectively raises awareness about environmental issues, it also reveals tensions between authentic advocacy and personal brand building. The research highlights how followers' interpretations of these messages can vary, sometimes focusing more on the celebrities' personal lives than on environmental content. This study contributes to the growing body of literature on celebrity activism in non-Western contexts and offers insights into the potential and limitations of using social media for environmental advocacy